Écriture réflexive et réflexion critique dans l’exercice du compte rendu - Serge Bibauw (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper addresses the issue of, supervised reflective writing in students’ general education. Through analyzing an electronic portfolio device where first year college students have to write reflective reports on extracurricular activities, we study how they carried out and perceived reflective and critical writing. Results tend to show some limits in reflective writing, when it is strictly supervised, compulsory and assessed. Nonetheless, the reflective report retains a significant value when fostering critical and in-depth use of student activities performed out of formal settings.